Epidemiological review of human and animal fascioliasis in Egypt - Maha F.M. Soliman (The Journal of Infection in Developing Countries, 2008)
One of the neglected food-borne-diseases in the international public health arena is fascioliasis. It is a serious infectious parasitic disease infecting humans and animals worldwide and tops all the zoonotic helminthes. Human cases are being increasingly reported from Europe, the Americas, Oceania, Africa and Asia. Hence, human fascioliasis is considered now as a zoonosis of major global and regional importance. In Egypt, animal and human fascioliasis is an endemic clinical and epidemiological health problem. Doubtless, understanding the epidemiology of the parasitic diseases and factors affecting their incidence provides the foundation upon which effective prevention and control programs should be established. This article reviews the history, life cycles, transmission, incidence, geographical distribution, and environmental and human determinants that contribute to the epidemiological picture of fascioliasis with special reference to Egypt.